2020
DOI: 10.1007/jhep09(2020)139
|View full text |Cite
|
Sign up to set email alerts
|

On Sugawara construction on celestial sphere

Abstract: Conformally soft gluons are conserved currents of the Celestial Conformal Field Theory (CCFT) and generate a Kac-Moody algebra. We study celestial amplitudes of Yang-Mills theory, which are Mellin transforms of gluon amplitudes and take the double soft limit of a pair of gluons. In this manner we construct the Sugawara energy-momentum tensor of the CCFT. We verify that conformally soft gauge bosons are Virasoro primaries of the CCFT under the Sugawara energy-momentum tensor. The Sugawara tensor though does not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…On each of these surfaces, the superrotation part of the extended algebra is given by the Witt algebra only if there are two particles/punctures. In this context, complementary aspects of the BMS group have been discussed in [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93].…”
Section: Jhep06(2021)079mentioning
confidence: 99%
“…On each of these surfaces, the superrotation part of the extended algebra is given by the Witt algebra only if there are two particles/punctures. In this context, complementary aspects of the BMS group have been discussed in [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93].…”
Section: Jhep06(2021)079mentioning
confidence: 99%
“…Therefore, since the energies ω * i do transform under SL(2,C), one may wonder whether the explicit dependence on the ω * i in the expression for h 5 in (2.43) could spoil the aforementioned covariance. The answer is of course not, since from (2.41) and the explicit expressions for f ij (see appendix A of [46]) one notices that they transform in such a way that the final evaluated expression for h 5 ({ω * i }, ω 5 ) ends up being conformal invariant. After evaluating h 5 ({ω * i }, ω 5 ) one obtains…”
Section: Jhep06(2021)171mentioning
confidence: 99%
“…This construction resembles the Sugawara construction of the energy momentum tensor for affine Lie algebras. See[37] for a recent discussion, where it was shown that the energy momentum tensor and supertranslation current[11] can be constructed as composite operators of conformally soft gluon states.…”
mentioning
confidence: 99%